DELINEATING THE IMAGINARY:THE SEMANTIC BASIN OF THE SPORTS OF ADVENTURE AND RISK - COICEIRO, GEOVANA ALVES; COSTA, VERA LUCIA DE MENEZES (Fiep Bulletin - online, 2014)
The institutionalized sport today reflects the moment that we are living, the pos modernity, an age of images. The modern sport that tried to give value to the pedagogical aspects of the greek sportive practice, giving importance to the health competition and loyal, the importance of the body and the physical activity based in a humanistic conception, gives place to a sportive practice based on the pleasure behavior, leading to a ephemeral practice, narcissist, where the man gives himself to the present and pleasure, to the consumism and individualism, typical behavior of pos modernity. The present article has the objective to delineate the imaginary of the "semantic basin" of the sports of extreme risk, showing the historical conception, cultural and social these practices started and consolidated. The theorical referentials were based on Durand (1982, 1983, 2003), Maffesoli (2001, 2002, 2003), Guiddens (1991, 2002), Berstein (1997), Costa (1999, 2000), Costa e Passos (2004, 2006). The six faces that define the "semantic basin", draining, division of water, confluences, name of the river, deltas and margins, were analysed . We conclude that the "semantic basin" of the sport of extreme risk begins between the XIX century and the beginning of the XX, period where it is possible to observe the first drainings be formed from the decadent symbols of modernity, such as: progress, rules, control, going against the new values of pos modernity: Uncertainity, risk, fun, imaginary. The mitogênica chain is characterized by different tribes, bur Dionisius reappear , institutionalizes and becomes burocractic, because it is under the form of Prometeu in the XIX century..